Who Would Subscribe for a Car? - The Influence of Car Ownership, Environmental Consciousness, Age, and Place of Living - Marvin Greifenstein; Felix Schakols; David Finken; Reto Hofstetter (Marketing Review St.Gallen, 2023)
This paper investigates the perceived trustworthiness and convenience of car subscriptions in Switzerland. Evidence has been found that age, car ownership and environmental consciousness of the respondents have a statistically significant impact on trust and perceived convenience while the place of living shows no effect.
Keywords: 650